The Role of Pharmacists in Antimicrobial Stewardship Programs (ASP) in Asia: A Literature Review - pande, ayu (Institut Teknologi dan Kesehatan Bintang Persada, 2024)
The Antimicrobial Stewardship Program (ASP) is a program aimed at optimizing the appropriate use of antibiotics in various healthcare institutions. A key requirement for implementing ASP is the presence of a multidisciplinary healthcare team, including pharmacists, due to their expertise in pharmacotherapy and knowledge of antimicrobials. This literature review aims to highlight the optimal role of pharmacists in enhancing ASP to combat antimicrobial resistance (AMR) in Asia. Research articles were retrieved using the PUBMED database with the keywords “antimicrobial stewardship program,” “pharmacist,” and “Asia,” combined with the Boolean operator “AND.” A total of eight research articles were included in the final review. No published evidence on ASP implementation in Indonesia was found. Pharmacist interventions in ASP activities were highly effective in several aspects, including improving antibiotic prescribing in accordance with the 5R principles (right drug, right dose, right route of administration, right timing, and right duration of antibiotic use), reducing hospital length of stay, lowering costs associated with antibiotic use or procurement, decreasing the proportion of adverse events related to antimicrobials, among others. Encouraging pharmacist involvement in ASP requires institutions to identify their specific gaps and challenges, particularly in Asia, and specifically in the Republic of Indonesia, to enable the direct implementation of the pharmacist's role in ASP.